A Comparative Analysis of Two Thermal Performance Assessment Methods for Labelling Residential Buildings The case study of Babolsar Houses - ماریا کردجمشیدی (صفه)
A policy to encourage building optimization and to reduce the building’s energy consumption is rating and labeling building’s energy performance which is usually based on the assessment of the building’s thermal performances. The building energy labeling method used in Iran differs from those introduced through international standards. The present paper aims to compare the two above methods. To achieve this objective, the thermal performance of 184 residential buildings are studied in the mild humid climate of Babolsar, using both modeling and “performance approach” methods. The modeling is done using Energy Plus software to predict annual energy requirements. The “performance approach” is methods prescribed by Chapter 19, National Iranian Building Regulations, to compute U-values. All buildings were labeled first based on their annual energy requirements then based on the proportion of building U value to the reference U value. The two ratings show a low correlation (0.2) between them with different labeling in 40% of cases. This renders revisions to the Iranian system inevitable. A combined labeling system is proposed in the conclusion.